A STUDY ON THE IMPACT OF BRICK EMBANKMENT ON AQUATIC ENTOMOFAUNA - PAHARI, PRITI RANJAN; JANA, GOPAL CHANDRA; MANDAL, SUDIPTA; MAITI, SUBHADEEP; BHATTACHARYA, TANMAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Shrinkage of the littoral zone due to brick embankment around a pond caused an adverse effect on the floral & faunal composition. A brick embanked pond (BEP) had lower number of macrophytes and entomofauna as compared to a natural pond (NP). Index of similarity suggests that both the ponds were strongly dissimilar in their floral and entomofaunal composition. Hemiptera was the most predominating insect order (96.73%) in BEP while Odonata (41.14%) and Coleoptera (39.02%) were the common orders in NP. Lower diversity, equitability, signal, ASPT, BMWP indices/scores and higher dominance & FBI indices in BEP as compared to NP indicates that BEP provided a less equitable habitat with poor quality of water for the existence of lower diversity of entomofauna.